Bacterial outer-membrane vesicles promote Vγ9Vδ2 T cell oncolytic activity - Firth, Jack; Sun, Jingjing; George, Vaques; Huang, Jian-Dong; Bajaj-Elliott, Mona; Gustafsson, Kenth (Frontiers in Immunology, 2023)
Increasing evidence suggests the immune activation elicited by bacterial outer-membrane vesicles (OMVs) can initiate a potent anti-tumour immunity, facilitating the recognition and destruction of malignant cells. At present the pathways underlying this response remain poorly understood, though a role for innate-like cells such as γδ T cells has been suggested. Peripheral blood mononuclear cells (PBMCs) from healthy donors were co-cultured with E. coli MG1655 Δpal ΔlpxM OMVs and corresponding immune activation studied by cell marker expression and cytokine production. OMV-activated γδ T cells were co-cultured with cancer cell lines to determine cytotoxicity. The vesicles induced a broad inflammatory response with γδ T cells observed as the predominant cell type to proliferate post-OMV challenge. Notably, the majority of γδ T cells were of the Vγ9Vδ2 type, known to respond to both bacterial metabolites and stress markers present on tumour cells. We observed robust cytolytic activity of Vγ9Vδ2 T cells against both breast and leukaemia cell lines (SkBr3 and Nalm6 respectively) after OMV-mediated expansion. Our findings identify for the first time, that OMV-challenge stimulates the expansion of Vγ9Vδ2 T cells which subsequently present anti-tumour capabilities. We propose that OMV-mediated immune activation leverages the antimicrobial/antitumour capacity of Vγ9Vδ2 T cells, an axis amenable for improved future therapeutics.